Evaluation of the Application of Modified Early Obstetric Warning Score in Maternal Patients at Sardjito General Hospital in 2019-2020 - Depari, Irmanda Terbelluh Sembiring; Nurdiati, Detty Siti; Attamimi, Ahsanudin (JURNAL KESEHATAN REPRODUKSI, 2024)
Background: Modified Early Obstetric Warning Score (MEOWS) is used to identify obstetric patients at risk of deterioration. MEOWS has long been used in the maternal ward of Dr. Sardjito Central General Hospital. Research in other countries found that MEOWS cards were not filled in completely and some MEOWS cards were not followed up.Objective: to determine the completeness of the MEOWS card and the suitability of the interventions carried out with the MEOWS card instructions.Methods: This study is a mixed method study (quantitative descriptive and qualitative phenomenology).Results: Out of 1285 study subjects, the proportion of complete MEOWS cards was 84.67%. The proportion of appropriate interventions was 95.05%. Appropriate intervention was associated with length of hospitalization ≥ 7 days, p value 0.043, prevalence ratio 0.456 (95% confidence interval 0.242-0.858). Reasons for staff not completing MEOWS cards and not performing appropriate interventions were management factors, lack of knowledge, compliance, vigilance, training and medical records.Conclusion: Most MEOWS cards were completed and appropriate interventions were performed. Appropriateness of MEOWS interventions is likely to reduce the prevalence of length of stay ≥ 7 days. MEOWS completion and interventions are influenced by staff management, knowledge, vigilance and compliance, which can be improved by training and practical use of medical records.